QUANTIFICATION OF THE EFFICIENCY OF RUMEN MICROBIAL PROTEIN SYNTHESIS IN STEERS FED GREEN TROPICAL GRASS - MULLIK, MARTHEN L.; POPP, DENNIS P.; McLENNAN, STUART R. (Majalah Ilmiah Peternakan, 2008)
ABSTRACT The rate of rumen microbial crude protein (MCP) supply to the intestines is a crucial element in the current rumen models to predict respond of ruminants to a certain diet. Data from tropical pastures always below predicted results from the existing rumen models. Thus, quantification of the rumen MCP supply from tropical grass will improve predictive rate under tropical feeding conditions. Four Brahman crossbred steers (457±20.1 kg) were used in a metabolism study. Pangola grass (Digitaria erianthe cv. Steudal) was harvested every morning and fed to the animals soon after. Parameters measured were EMPS, intake, fractional passage rates, and rumen ammonia concentration. The EMPS was estimated using purine derivative excretion in urine. Crude protein and water soluble carbohydrates content were 6.3 and 7.4% of dry matter (DM) respectively. DM intake was 1.6% live weight. Average rumen ammonia concentration was 69 mg/L whilst rumen passage rates were 7.84 and 6.92 %/h for fluid and solids respectively. EMPS was only 72 g MCP/kg digestible organic matter. It might be concluded that EMPS in steers consuming green pangola grass was below the minimum level for forage diets adopted in the current feeding standards. ABSTRAK Tingkat pasokan protein mikroba rumen (MCP) ke usus halus merupakan salah satu unsur kunci dalam meramal respon pertumbuhan ruminan terhadap ransum tertentu. Data MCP hijauan tropis selalu berada di bawah nilai prediksi model rumen yang dipakai saat ini. Dengan demikian, kuantifikasi pasokan MCP rumput tropis diharapkan menjadi masukan untuk meningkatkan kemampuan prediksi model rumen untuk pakan daerah tropis. Empat sapi jantan muda Brahman persilangan (457±20,1 kg) digunakan dalam sebuah penelitian metabolisme. Rumput pangola (Digitaria erianthe cv. Steudal) dipanen setiap pagi dan langsung diberikan kepada ternak dalam kandang metabolis. Parameter yang diukur adalah produksi MCP dan efisiensi sintesis MCP (Emps), konsumsi, laju alir digesta, dan konsentrasi amonia rumen. Nilai EMPS diestimasi menggunakan turunan purin dalam urin. Kandungan protein kasar dan karbohidrat mudah larut adalah 6.3 % and 7.4%. Rata-rata konsumsi BK adalah 1.6% berat badan. Konsentrasi amonia rumen 69 mg/L, sedangkan laju alir digesta cair sebesar 7.84 %/jam and padat sebesar 6.92 %/jam. Rata-rata EMPS hanya 72 g MCP/kg bahan organik tercerna. Disimpulkan bahwa nilai EMPS untuk rumput tropis segar yang dikonsumsi oleh sapi jantan berada di bawah nilai standar hijauan yang dipedomani dewasa ini.